Current and novel injectable hydrogels to treat focal chondral lesions: Properties and applicability. Issue 1 (22nd November 2017) - Pascual‐Garrido, Cecilia; Rodriguez‐Fontan, Francisco; Aisenbrey, Elizabeth A.; Payne, Karin A.; Chahla, Jorge; Goodrich, Laurie R.; Bryant, Stephanie J.
ABSTRACT: Focal chondral lesions and early osteoarthritis (OA) are responsible for progressive joint pain and disability in millions of people worldwide, yet there is currently no surgical joint preservation treatment available to fully restore the long term functionality of cartilage. Limitations of current treatments for cartilage defects have prompted the field of cartilage tissue engineering, which seeks to integrate engineering and biological principles to promote the growth of new cartilage to replace damaged tissue. Toward improving cartilage repair, hydrogel design has advanced in recent years to improve their utility. Injectable hydrogels have emerged as a promising scaffold due to their wide range of properties, the ability to encapsulate cells within the material, and their ability to provide cues for cell differentiation. Some of these advances include the development of improved control over in situ gelation (e.g., light), new techniques to process hydrogels (e.g., multi‐layers), and better incorporation of biological signals (e.g., immobilization, controlled release, and tethering). This review summarises the innovative approaches to engineer injectable hydrogels toward cartilage repair. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:64–75, 2018. Abstract : Injectable hydrogels have emerged as a promising scaffold for cartilage regeneration due to their wide range of properties, their ability to encapsulate cells and for providing cues for cell differentiation. Some of these advances include the development of improved control over in situ gelation (e.g., light), new techniques to process hydrogels (e.g., multi‐layers), and better incorporation of biological signals (e.g., immobilization, controlled release, and tethering). This review summarizes the innovative approaches to engineer injectable hydrogels toward cartilage repair.